The role of aging and various surface preparation methods in the repair of nanohybrid composites - Ayşenur Altuğ Yıldırım; Mine Betül Üçtaşlı (BMC Oral Health)
Abstract Background Repairing composite resins is a less invasive alternative to complete restoration replacement. To achieve a successful bond between the existing and newly applied composite materials, various surface preparation methods, such as sandblasting and acid etching, have been explored. The aim of the study was to evaluate the effect of different surface treatments on the repair bond strength of a universal nanohybrid composite resin restorative material before and after thermal aging, by utilizing a micro-shear bond strength (µSBS) test. Methods For the micro-shear bond strength test, a total of 120 cylindrical (3mmX2mm) nanohybrid resin based composite specimens were prepared. The prepared specimens were divided into three groups (n = 40/per group) based on surface treatment methods: a non-aged group, 10,000 thermal cycle aging and 50,000 thermal cycle aging. The aged and non-aged specimens were further divided into four groups according to adhesive application modes and surface pretreatment methods: 1.universal adhesive/self-etch mode, 2.aluminum oxide sandblasting + universal adhesive/self-etch mode, 3.universal adhesive/etch-and-rinse mode, 4.aluminum oxide sandblasting + universal adhesive/etch-and-rinse mode. Subsequently, 0.8mmX2mm disc shape light cure resin based composite specimens were applied with a direct placement technique on the treated surfaces of all samples for repair. µSBS test was performed using a universal testing machine at a crosshead speed of 1 mm/min. Kruskal-Wallis and Mann-Whitney tests were performed for statistical analysis. Results The µSBS values of the non-aged group were higher than those of the 10,000 and 50,000 thermal cycle groups, with no significant differences within the non-aged subgroup (p > 0.05). In the aged groups, significant differences were observed between adhesive application modes and surface treatments. Specifically, the etch-and-rinse mode showed higher bond strengths than the self-etch mode after 50,000 thermal cycles (p < 0.05). Sandblasting combined with universal adhesive (self-etch mode) improved bond strength, especially in the 10,000 thermal cycle group (p < 0.05). Conclusion Aging reduced the bond strength of composite resin repairs, with the etch-and-rinse mode outperforming the self-etch mode in aged specimens. Sandblasting alone did not enhance bond strength. These findings highlight the importance of considering aging and adhesive strategies to optimize repair outcomes, with further research needed on long-term durability.